Reduction in the frequency of Aspergillus spp. in broiler facilities subjected to cleaning and disinfection - BURBARELLI,Maria Fernanda de Castro (2020)
ABSTRACT The present study analyzes influence of two cleaning and disinfection protocols on frequency of Aspergillus spp. in broiler facilities. We conducted an observational study, applying two cleaning and disinfection protocols before housing 960 one-day-old broilers randomly allocated in 32 boxes with 30 birds. We considered two types of housing as independent experiments, which differed as to the bedding. First experiment consisted of new bedding materials, which we reused in second experiment. We applied two different treatments, Common treatment included sweeping organic matter, humidifying residual material with low pressure water, washing with water and neutral detergent, with posterior rinsing. European treatment was according to the standards of the manufacturer of disinfectants. Procedures included dry and humid organic matter removal, humidification, washing with high pressure water, application of detergent, rinsing, and application of two compound disinfectants: glutaraldehyde (250 g/L) + formaldehyde (185 g/L); p-chloro-m-cresol (210 g/L). To evaluate the presence of Aspergillus spp., we collected samples from surfaces and equipment before and after cleaning and disinfection, at 7, 14, 28, and 42 days of experimental period. Mycological assessment included streaking on Petri dishes containing AFPA (Aspergillus Flavus and Parasiticus Agar, Sigma Aldrich®). Common cleaning and disinfection treatment led to a higher presence of fungus in floors and walls (83% vs. 0% p = 0.0030 and 50% vs. 0% p = 0.0450) in first and second experiments, respectively. As this study demonstrates by using the European procedures, performing a detailed cleaning and disinfection protocol reduces the presence of Aspergillus spp. in broiler facilities.